7 Pre-clinical studies in a novel side-branch stent. (27th November 2017) - Banning, Amerjeet S; Gariety, Vincent; Mouniemne, Karim; Janus, Justyna; Kelly, Michael; Gunn, Julian P; Gershlick, Anthony H
Abstract : Background: Bifurcation lesion stenting remains an area for translational research focus, since provisional stenting, while commonly used, may be inadequate in many cases and currently available 'bifurcation' stents are limited. Methods: We have developed a novel side branch stent with a modifiable end through controlled longitudinal shortening, allowing adaptation to any bifurcation angle. Results: Design optimisation and computational finite element analysis resulted in good virtual bifurcation apposition. Safety testing data informed laser-cutting of cobalt chromium prototypes with appropriate tensile stress characteristics, and deployed in silicone bifurcation model -λ and Y shapes at 60 o, 45 o angles, MicroCT showed only 2.8% mal-apposed struts; mean wall distance 0.03±0.02 mm. Mechanical testing showed low recoil (4.01%±1.31%) and foreshortening (2.15%±0.68%) and good radial strength (malleable end 0.21±0.01 N/mm, regular part=0.24±0.01 N/mm). The optimally performing prototype ( Iteration7 ) was deployed in 20 porcine coronary bifurcations, with initial MicroCT indicating minimal stent protrusion into main/side branch lumen and complete bifurcation angle coverage (figure 1). Conclusion: 4 years of bench, in-vitro and in-vivo studies show proof-of-concept that an in-vivo modifiable stent can be used to stent coronary bifurcation side-branches. Work towards first-in-man studies is on-going.